The reactivity of nanoporous alumina towards selected Knoevenagel condensation reactions - Ramli, Zainab (Faculty of Science, Universiti Teknologi Malaysia, 2009)
In this study, ordered nanoporous alumina in mesopore size range was prepared by easy and fast precipitation method using inexpensive inorganic aluminium salt with ammonium acetate (NH4(CH3COO)) as precipitating agent. The prepared mesoporous alumina produced showed high surface area with narrow pore size distribution (FWHM =2.5 nm) centred at 8.5 nm. The pyridine adsorption proved that the mesoporous alumina exhibits Lewis acidity. The reactivity of the mesoporous alumina was tested in the selected Knoevenagel condensation reaction of cinnamaldehyde with malononitrile and methyl cyanoacetate. The synthesized mesoporous alumina was found to be more active in the reaction between cinnamaldehyde and malononitrile with 89% conversion and 93% selectivity of the desired product. However, the reaction between cinnamaldehyde and methyl cyanoacetate only produced 32% conversion and 86%selectivity. The activation temperatures of the catalyst did not affect the reactivity of the mesoporous alumina in the selected Knoevenagel reactions.